Visible Light Mediated, Photocatalyst-Free Condensation of Barbituric Acid with Carbonyl Compounds - Kumari S.; Kumar Maury S.; Kumar Singh H.; Kamal A.; Kumar D.; Singh S.; Srivastava V. (My University, 2025)
An economical and efficient method has been developed for the production of dibarbiturates of oxindole and arylidene barbituric acid derivatives via condensation of of isatin/aryl aldehyde with barbituric acid, through irradiation of visible light. Under the similar conditions 2 molecules of barbituric acid react with 1 molecule of isatin while only 1 molecule of barbituric acid reacts with 1 molecule of aldehyde. This transformation involves catalyst free pathway for the formation of desired products under mild reaction conditions. Metal free reaction conditions, high yield of products along with the absence of side-products are additional green features of this protocol. © 2021 Wiley-VCH GmbH